Dampak Banjir Tahun 2012 terhadap Masyarakat Kota Padang: Studi Sejarah Lingkungan - Betri Gusnita; Hendra Naldi (Jurnal Kronologi, 2026)
Padang is the capital of West Sumatra Province, located on the west coast of Sumatra Island. Padang consists of 8 districts. It is traversed by 5 major rivers and 16 minor rivers. It has an average rainfall of 296.00 mm/month (2015) and relatively low temperatures throughout the year. Padang City is situated on swamps and rumbia forests, and combined with its high rainfall, this makes Padang City prone to flooding. Based on data from DIBI BNPB, since 2009-2024 there has been an increase in flooding incidents in Padang City. Based on a hazard index assessment by KRB Padang City, almost the entire area of Padang City is threatened by flooding, covering an area of approximately 14,901 hectares. The vulnerability to flooding in Padang City will have a significant impact on the community of Padang City itself. These impacts include economic losses, health problems, and even loss of life. This study aims to identify the impacts of the 2012 flash floods on the people of Padang City. The research location is in the area of Padang City that was affected by the 2012 flash floods. This study uses a historical research method with data collection techniques through interviews. Based on the results of this study, there are several impacts of flooding experienced by the people of Padang City, which are divided into four parts. First, economic losses. Second, the disruption of community activities. Third, the most common health impact is the emergence of anxiety among people living in areas that are prone to flooding every year. Fourth, the impact on the environment, which results in the loss of land function in areas affected by flooding.